Laure Prouvost’s Deep See Blue Surrounding You: An Immersive Environment Made of Objects (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2023)
This paper aims to demonstrate how Laure Prouvost’s artistic practice requires an immersion of the viewer in intermedial installations composed of objects from the most disparate spatial and temporal origins. Since the early 2000s, the French artist has intentionally created surreal mise-en-scenes which, by blending video, painting, drawing, sculpture, and performance, can be understood as compositions or collages made of visual references taken from different contexts such as pop culture, the web, and private photo albums. Prouvost’s works are “unstable visual entities,” made of images that aggregate in heterogeneous configurations, generating eccentric atmospheres and cancelling every hierarchical order between the observer and the observed. Viewers are encouraged to fill the space by becoming objects among other objects. By using the Object-Oriented Ontology (OOO) as philosophical and methodological support, this paper will focus more closely on the analysis of Deep See Blue Surrounding You / Vois Ce Bleu Profond Te Fondre (2019), the project Prouvost produced for the French Pavilion at the 58th Venice Biennale. On this occasion, her work They Parlaient Idéale (2019) – a video documenting the Mediterranean Sea journey that brings her to the Venetian lagoon – was the cornerstone of a multifaceted environmental installation. Assuming a critical and analytical approach, this contribution then discusses the role Deep See Blue Surrounding You plays as a “hyper-enactment:” it is a mise-en-scene that consists of interrelationships between “things/images” that aggregate as objects, but it is also a composition in which the viewers are “viscously” asked to generate their personal, non-linear narration.
Keywords: Laure Prouvost; Surrealism; Object-oriented ontology; Hyper-enactment; Venice Biennale